Komitmen Organisasi Memoderasi Pengaruh Sistem Akuntansi Keuangan Daerah terhadap Kualitas Laporan Keuangan - Ratifah, Ifa; Ridwan, Mochammad (Jurnal Trikonomika, 2012)
BPK report in 2011 on the financial statements of local government show there are 1401 case of weakness due to accounting and reporting. This poses problems for local governments to improve the quality of financial reporting is characterized by the release of opinion. Implementation of the financial accounting system will not be adequate without the support of the organizationâs commitment in creating good quality financial statements. This study examined the effect of the regional financial accounting system on the quality of financial statements with organization commitment as moderating variable. Data were collected from 28 of the accounting department in Kabupaten Karawang. Data were analyzed using Moderated Regression Analysis (MRA). The results of empirical studies indicate that theregional financial accounting system has a significant effect on the quality of financial reporting. Similarly, by adding commitment of the organization as moderating variable, the regional financial accounting system has a significant effect.